PENGARUH TERPAAN TAYANGAN BERITA KASUS KEKERASAN SEKSUAL PADA ANAK DI TELEVISI TERHADAP TINGKAT KECEMASAN ORANGTUA DI SD AL-ULUM - Ghea Alifia Putri; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
News in television has advantages of radio news or news paper. Currently various news information program is needed by everyone. News become very important because it deals directly with the lives of their audience. The sexual violence cases were often becomes the hot news to attract the curiosity of community. Of all the curiosity, fear and anxiety are the most subject of community complain, especially for parents. In association with cultivation theory which states that the more time a persons spends watching television, the stronger the tendency of people equate social reality. At this point respondents who often watch the news that shows cases of sexual assault on a child on television tend to be anxious. The purpose of this study is to observe how much the level of anxiety parents in SD Al-Ulum of exposure to the news which shows cases of sexual assault on a child on television.The method used in this study is a quantitative method with explanation survey. Researchers collected data using questionnaires and documentation. The location of this research is in kota Pekanbaru. The number of samples for this study as many as 96 respondents, using sampling techniques unknown population because the population of responden who is watching news exposure on child sexual assault cases on television is not known for certain. To determine the effect of these two variables, researchers used a simple linear regression analysis. While the questionnaire for processing test data, performed using the Statistical Product and Service Solutions (SPSS) Windows version 20.Based on a simple linear regression to study the influence of the news exposure on child sexual assault cases on television of parental anxiety at SD Al-Ulum, the regression coefficient values obtained in this study is Y = 15.236 + 0.803 X with a significance level of 0.0001 and smaller than α = 0.05. While based on the determination test, the result is 34.8 %. It means, there is a small influence of exposure to the news that shows cases of sexual assault on a child on television to the level of anxiety of parents in SD Al-Ulum. The dominant respondents work as civil servants and private employees, so there is not much time to watch the news that shows cases of sexual assault on a child on television.Keywords: News,Child Sexual Assault Cases, Parental Anxiety